1997
DOI: 10.1046/j.1365-3180.1997.d01-18.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dissipation of atrazine in soils taken from various maize fields

Abstract: Summary A laboratory study was carried out in order to measure the degradation rate of atrazine in 36 different soils taken from maize (Zea mays L.) fields in Belgium. These soils differed in their alrazme treatment histories. pH. organic matter content and type of organic and mineral fertili‐zation, Half‐lives of less than 10 days were found in more than 60% of the soils sampled. This rapid dissipation could be linked in a significant way to repeated pretreaiments with atrazine (intensive maize cropping) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 13 publications
4
51
1
1
Order By: Relevance
“…This is consistent with findings of a microbial transformation of parthenin (Bhutani and Thakur 1991;Abdel Halim et al 2007), and it points to the possibility of enriching soils with microorganisms that are capable of degrading parthenin, a phenomenon that is well known from several commercial herbicides (Walker et al 1993;Pussemier et al 1997). Hence, it was no surprise that soil samples previously infested with P. hysterophorus showed on average a 6-fold higher capacity to degrade parthenin than adjacent, uninfested soils.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with findings of a microbial transformation of parthenin (Bhutani and Thakur 1991;Abdel Halim et al 2007), and it points to the possibility of enriching soils with microorganisms that are capable of degrading parthenin, a phenomenon that is well known from several commercial herbicides (Walker et al 1993;Pussemier et al 1997). Hence, it was no surprise that soil samples previously infested with P. hysterophorus showed on average a 6-fold higher capacity to degrade parthenin than adjacent, uninfested soils.…”
Section: Discussionsupporting
confidence: 86%
“…However, the ability to utilize the herbicide as a carbon source should be a significant selective advantage in atrazine- treated soil. Our results and the results of other recent studies indicate that atrazine-mineralizing bacteria are now widespread in soils that are subjected to conventional agricultural management practices and that the activity and abundance of these organisms may be enhanced by repeated application of the herbicide or by simple soil management practices, such as manure application (3,50,53,64). Several of our isolates, all of which contained atzABC, completely mineralized atrazine and converted ring 14 C to 14 CO 2 .…”
Section: Discussionsupporting
confidence: 73%
“…Persistence generally declines in response to herbicide use, suggesting that exposure of soil to atrazine enhances the abundance and activity of atrazine-degrading bacteria (3,50,53). The objectives of the work reported here were to isolate bacteria from soils which rapidly degrade atrazine and to characterize these bacteria with respect to their diversity, identity, and mechanism of atrazine degradation.…”
mentioning
confidence: 99%
“…Y57 (Sun et al 2006), which was isolated from the soil collected from Changzhou, were obtained from different soils collected from three different herbicide-manufacturing plants, however all of these three soils had been contaminated by isoproturon for a long time. The isolation of these strains suggested that exposure of soil to herbicide enhances the abundance and activity of herbicide-degrading bacteria (Ostrofsky et al 1997;Pussemier et al 1997). Since several different bacteria that have the ability to mineralize phenylurea herbicides have been recently isolated (Dejonghe et al 2003;El-Sebai et al 2004;Sorensen et al 2001;Widehem et al 2002), these earlier studies together with the work described here, indicate that different strains belonging to different genera are involved in the metabolism of phenylurea herbicides, but all these strains had different characteristics of extent and degree of degradation.…”
Section: Discussionmentioning
confidence: 99%